THE ROLE OF GOVERNMENT IN THE FORMATION OF LOCAL WISDOM BASED BUSINESS LEGAL REGULATIONS IN INDONESIA - Marina, Liza; Anam, Saiful; Haliding, Safri; Nugroho, Wahyu; Yulia, Aris (Universitas Lampung, 2025)
Business law in Indonesia is predominantly shaped by the civil law tradition of continental Europe, resulting in regulations that often overlook local needs and values. The uncritical adoption of foreign legal norms has marginalized indigenous legal traditions, which historically embody principles of ethical commerce and community-based practices. This misalignment between formal regulation and local business conduct creates legal uncertainty, discourages domestic investment, and undermines the competitiveness of local entrepreneurs. To address these challenges, business law reform must integrate cultural values such as consensus-based decision-making (musyawarah), mutual cooperation (gotong royong), distributive justice, and social responsibility, while remaining adaptive to globalization and economic liberalization. Employing a normative legal research method with conceptual and statutory approaches, this study analyzes the integration of local wisdom into business law to strengthen inclusivity, contextual relevance, and sustainability. The findings are expected to contribute theoretically and practically to a national business law framework that not only reflects Indonesia’s constitutional identity but also preserves local culture and reinforces grassroots economic sovereignty.